Borges and the North - Brljak, Vladimir (Array, 2011)
The paper presents an overview of Jorge Luis Borges’s involvement with Old Germanic cultures and literatures, outlining a remarkable chapter in the history of twentieth-century medievalism. It traces the development of Borges’s northernism and shows his northernist-inspired opus to be not only much more extensive – over one hundred items are listed which are either partly, and a good number of them wholly, northernist in inspiration – but also more variegated, complex and important than previous inquiries have indicated. Among other topics, the paper examines and explicates northernist references and echoes found in Borges’s literary work, discusses his scholarly efforts in the field, and reflects on his increasingly personal involvement with the North in the final decades of his life.